A Study on Relaxation Learning Factory in Vocational Higher Education During the covid-19 Endemic Transition - Gregorius Adi Prastiantomo; Tri Hannanto Saputra; Agus Wijayanto (Poltanesa, 2023)
Vocational Higher Education in providing quality vocational higher education is inseparable from its education model that implements PBET (Production Based Education and Training). To support this educational model, Vocational Higher Education has an educational facility called the Learning Factory. The concept of Learning Factory is facing challenges due to the extraordinary events post of the COVID-19 pandemic. Organizational strategic management is needed in relaxing concepts and activities related to the learning factory in Vocational Higher Education. Organizations must be able to formulate strategic policies that focus on the health and safety of students during the COVID-19 pandemic. Relaxation is a way or action to align the mind in a constructive direction so that what you want can be achieved. The main changes needed in Learning Factory Relaxation are the Implementation Model and the Learning Matrix. Both require Authorization in a process that supports teaching activities and the desired result. Therefore, principles are needed to support the achievement of modules that are open to the entire learning process and make prototypes for vocational students. As a form of a new breakthrough with technology in the industrial sector and getting around the adaptation of new habits during the Covid-19 pandemic, the learning process must be developed more innovatively and continues to be productive for the sake of mutual welfare. In realizing adaptive relaxation, it is necessary to focus on assessing the functions of Technoware, Infoware, Humanware, and Organware (THIO) as tools that Vocational Higher Education can use to improve services to stakeholders.